Pematahan Dormansi Umbi Bawang Putih (Allium sativum L.) Varietas Lumbu Hijau dengan Perlakuan Lama Penyimpanan Umbi pada Suhu Rendah dan Aplikasi Giberelin - Diah Rochana Puspitasari; Anne Nuraini; Sumadi Sumadi (Paspalum: Jurnal Ilmiah Pertanian, 2020)
Low temperature and gibberellin treatments affected on breaking dormancy. The effects of low temperature in storage duration and gibberellin treatrments on breaking of dormancy of garlic were examined in this study. The aims of this study to determinate the best treatments for breaking garlic bulb dormancy. The sorted garlic bulbs were stored at 4 ± 0.4 ° C for 0 (control), 15, 30 and 45 days. The bulbs that have been treated by low temperature then treated by gibberellins at various concentrations including 0, 75, 150, and 225 mgL-1 by soaking for 24 hours. The bulbs were  planted in the seedling house. The low temperature storage (4±0,4ᵒC) for 45 days is more effective than 0, 15 and 30 days, while the concentration of gibberellins were not have a significant effect on breaking dormancy.  GA3 endogenous was increased during low temperature storage, on the other hand, it accelerated on breaking dormancy . The highest percentage of sprouting  bulb produced by treatment at low temperature storage for 45 days. Growth parameters such as shoot length, shoot dry weight and leaves get the best at 45 days storage time. Low temperature storage (4±0,4ᵒC) is effective in breaking dormancy of garlic bulb.